ANALISIS SOSIAL EKONOMI TERHADAP PENGANGGURAN MUDA DI SUMATERA BARAT - Suci Mutiadanu; Melti Roza Adry; Dewi Zaini Putri (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2018)
The research aims to determine the effect of  gender, marital status, level of education, economic growth, agricultural sector, trade sector, and services to the dependent variable of youth unemployment in West Sumatra. The type of this research is descriptive research, where the data used is secondary data in the form of cross-section data with national workforce survey data 2015. By using logistic regression analysis method, the results of this study indicate that Gender has positive and significant effect on youth unemployment in West Sumatra, Marital status has a negative and significant effect on youth unemployment in West Sumatra, Level of education has positive and significant effect on youth unemployment in West Sumatra, Economic growth hasnegative and significant effect on youth unemployment in West Sumatra, Agricultural sector has a negative and significant effect on youth unemployment in West Sumatra, Trading sector has a negative and significant effect on youth unemployment in West Sumatra, and Service sector has a negative and significant effect on youth unemployment in West Sumatera.